Enjoying what we don't have : the political project of psychoanalysis - McGowan, Todd (Symplokē studies in contemporary theory., 2013)
Although there have been many attempts to apply the ideas of psychoanalysis to political thought, this book is the first to identify the political project inherent in the fundamental tenets of psychoanalysis. And this political project, Todd McGowan contends, provides an avenue for emancipatory politics after the failure of Marxism in the twentieth century. Where others seeking the political import of psychoanalysis have looked to Freud's early work on sexuality, McGowan focuses on Freud's discovery of the death drive and Jacques Lacan's elaboration of this concept. He argues that th.